The Effectiveness and Strategy Aqidah Akhlak Teacher in Online Learning MAN 10 Jombang - Mohammad Saat Ibnu Waqfin; Roikhatul Jannah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Education must continue to be implemented even with online learning, so that the golden generation does not lag behind in knowledge and continues to learn for the advancement of the next generation as the buds of the nation's progress in the future. As for the formulation of the problem in this research are (1) How is the effectiveness of online learning in the subject of aqidah akhlak in MAN 10 Jombang, and (2) What is the online learning strategy for teachers of aqidah akhlak subject in MAN 10 Jombang. This type of research is included in the type of field research (field research) which is qualitative with descriptive research methods. Data collection procedures were carried out by means of observation, interviews, questionnaires, and documentation, then data analysis used data reduction, data presentation, and drawing conclusions. Based on the research results, it was found that online learning has not been effective, therefore the teacher's efforts in increasing the effectiveness of online learning are by using appropriate methods and media, besides giving assignments by giving a certain period of time. Then for the strategy used by the aqidah akhlak subject teacher is to use the PAKEM strategy and the methods used are lectures, discussions, question and answer, and assignments. In addition, another teacher strategy is to provide motivation and rewards or rewards to students.